Relationship between characteristics and the level of public knowledge about hypertension self-medication in kepala sungai village, dusun iii kayu lima, secanggang district, 2023 - Panjaitan, Nurhikmah; Pratama, Bagas Rizky (Institute Of Computer Science (IOCS), 2024)
Self-medication is the biggest effort made by the community to deal with health complaints independently, starting from recognizing the symptoms and illnesses they are experiencing to choosing a treatment method. The level of public knowledge about the use of medicines and types of herbal plants are known to be able to treat various diseases because they have relatively few side effects compared to chemical medicinal compounds. Hypertension is a degenerative disease and is a disease that is experienced by many people. Self-medication is the method most people use to deal with health problems before going to health service units in several areas or buying medicines at the nearest pharmacy without advice from a doctor. This study aims to determine the level of non-recommendation from a doctor. This research aims to determine the level of community knowledge about hypertension self-medication in the village of Head Sungai Dusun III Kayu Lima Secanggang District in 2023. This research is non-experimental with a quantitative descriptive type of research and the type of data used is primary data with the tool used in the form of a questionnaire with the average community aged 35 -70 years.Characteristics of respondents based on knowledge, the majority with a sufficient level of knowledge were 21 people (48.80%) and the minority with a good level of knowledge was 3 people (7.00%). The conclusion from this research is that there is no significant relationship between sociodemographics.